Threat-Modulation of Executive Functions—A Novel Biomarker of Depression? - Peräkylä, Jari; Järventausta, Kaija; Haapaniemi, Piia; Camprodon, Joan A.; Hartikainen, Kaisa M. (Frontiers in Psychiatry, 2021)
Background: Alterations in executive functions, emotion regulation and their interaction are common concomitants of depression. Executive dysfunction frequently lingers after treatment, has adverse effects on daily life and predisposes to recurrence of depression. Yet, sensitive measures of executive function for reliable assessment of cognitive outcomes are still lacking in clinical practice. To better understand the impact of depression and its most effective treatment, electro-convulsive therapy (ECT), on cognition we assessed executive functions pre- and post-ECT and whether objective measures reflecting alterations in emotion-executive function interaction correlate with depression severity or with cognitive outcome. Methods: Executive functions were assessed in 21 patients with major depressive disorder (MDD) before and after ECT using subjective measures from Behavior Rating Inventory of Executive Function – Adult version (BRIEF-A), and objective cognitive performance measures derived from computer-based test of executive function, Executive Reaction Time (RT) test. In addition, we crated novel indices reflecting emotional modulation of cognitive performance by subtracting different performance measures in the context of neutral distractors from those in the context of threat-related distractors. We correlated these indices with Beck Depression Inventory (BDI) and BRIEF-A scores. Results: Depression was significantly alleviated, and executive functions improved post-ECT, as seen in reduced BDI-scores, BRIEF-A scores and number of errors in Executive RT-test. Pre-ECT BDI-scores correlated with threat modulation of RT (tmRT) and threat modulation of working memory (tmWM). Post-ECT tmRT correlated with several Behavioral Regulation scales and tmWM with several Metacognition scales of BRIEF-A. Conclusion: While caution is warranted, results from both subjective and objective measures suggest ECT that significantly improves executive functions and emotion regulation along with alleviation of depression. Novel indices derived from threat modulation of executive function and working memory show promise as objective biomarkers of depression severity pre-ECT and cognitive outcome post-ECT with potential for guiding depression treatments.